Evaluation of the Epidemiological Effectiveness of a Quadrivalent Inactivated Split Influenza Vaccine in the 2023–2024 flu season - R. V. Polibin; T. S. Saltykova; А. А. Pozdnyakov; V. A. Korshunov; A. G. Saltykova; N. I. Briko (Эпидемиология и вакцинопрофилактика, 2025)
Relevance. A distinctive feature of the influenza is the risk of severe complications, including cardiovascular (myocarditis or pericarditis) and nervous (encephalitis, meningoencephalitis and arachnoiditis) systems. Vaccination against influenza can significantly reduce the risk of disease, including complications and deaths.The aim of our study was to evaluate the epidemiological effectiveness of a quadrivalent inactivated split influenza vaccine in the 2023 –2024 season.Materials and methods. The study investigated the effectiveness of the tetravalent inactivated split vaccine Ultrix Quadri®. Vaccination data were collected in the regions of the Russian Federation as of January 1, 2024, in which a statistically significant amount of Ultrix Quadri® vaccine was used. The work was carried out using methods of variational statistics. The indicators of relative and attributive risks were evaluated, the Cochrane-Mantel-Hensel approach was applied, taking into account the assessment of heterogeneity of the results, and the effectiveness of the vaccine was evaluated.Results. The study showed that the risk of getting the flu among those vaccinated with Ultrix Quadri® vaccine was 122 (88-170) times lower than in those not vaccinated, which indicates the high epidemiological effectiveness of the vaccine. Cases of influenza among those vaccinated were observed in December 2023 - January 2024, that is, at the beginning of the epidemic season, during the period of the greatest rise in morbidity. At the same time, in absolute terms, their number was minimal. (414 cases out of 9.7 million vaccinated). From February to June 2024, the incidence of influenza among those vaccinated with the studied vaccine (with the exception of isolated cases) was not recorded.Conclusion. The conducted study demonstrated the high real epidemiological effectiveness of the Ultrix Quadri® vaccine during the epidemic season of influenza and ORI 2023/2024.